Endothelial microparticles are increased in congenital heart diseases and contribute to endothelial dysfunction. Issue 1 (December 2017) - Lin, Ze-Bang; Ci, Hong-Bo; Li, Yan; Cheng, Tian-Pu; Liu, Dong-Hong; Wang, Yan-Sheng; Xu, Jun; Yuan, Hao-Xiang; Li, Hua-Ming; Chen, Jing; Zhou, Li; Wang, Zhi-Ping; et al.
Abstract Background We previously demonstrated that endothelial microparticles (EMPs) are increased in mitral valve diseases and impair valvular endothelial cell function. Perioperative systemic inflammation is an important risk factor and complication of cardiac surgery. In this study, we investigate whether EMPs increase in congenital heart diseases to promote inflammation and endothelial dysfunction. Methods The level of plasma EMPs in 20 patients with atrial septal defect (ASD), 23 patients with ventricular septal defect (VSD), and 30 healthy subjects were analyzed by flow cytometry. EMPs generated from human umbilical vascular endothelial cells (HUVECs) were injected into C57BL6 mice, or cultured with HUVECs without or with siRNAs targeting P38 MAPK. The expression and/or phosphorylation of endothelial nitric oxide synthase (eNOS), P38 MAPK, and caveolin-1 in mouse heart and/or in cultured HUVECs were determined. We evaluated generation of nitric oxide (NO) in mouse hearts, and levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in cultured HUVECs and in mice. Results EMPs were significantly elevated in patients with ASD and VSD, especially in those with pulmonary hypertension when compared with controls. EMPs increased caveolin-1 expression and P38 MAPK phosphorylation and decreased eNOS phosphorylation and NO production in mouse hearts. EMPs stimulated P38 MAPK expression, TNF-α and IL-6 production, which were all inhibited by siRNAs targeting P38 MAPK in cultured HUVECs. Conclusions EMPs were increased in adult patients with congenital heart diseases and may contribute to increased inflammation leading to endothelial dysfunction via P38 MAPK-dependent pathways. This novel data provides a potential therapeutic target to address important complications of surgery of congenial heart disease.